The calculation of the hourly direct solar radiation incident on tilted, horizontal and vertical surfaces in Lattakia city - Karfoul, Rizek (Latakia University Journal -Basic Sciences Series, 2019)
In this research, a mathematical method was established by means of a computer to calculate the quantity of the hourly solar radiation incident on tilted, horizontal and vertical surfaces in Lattakia city, which can be applied for the unit area to use the photovoltaic cell panels in order to produce electrical energy required to provide energy the loaded needed. Some special data is considered as the height above sea level, the longitude, the latitude and the slope angles, and the order of the days in the year. The results showed that the direct radiation quantity incident on Lattakia city was rating between [945-0] W/m2. The study also proves that the slope angle affects reflexively on the hourly direct radiation quantity.